Assessing Environmental Drivers of the Distribution of the Rare Species Johannesteijsmannia altifrons: a literature review - Siregar, Etti Sartina; Djaingsastro, Aulia Juanda (International Journal of Ecophysiology, 2025)
Johannesteijsmannia altifrons, a palm species exhibits unique dispersal mechanisms and distribution patterns that are critical to understanding its ecological dynamics. Dispersal has a significant impact on this species' spatial distribution and population dynamics. The distribution is significantly influenced by altitude, which affects its growth and habitat suitability. Publications and references in this analysis came from scientific articles published in bibliographic databases such as Scopus and Google Scholar. The keyword search used was â€œJohannesteijsmannia altifronsâ€. The authors examined the literature related to the subject of the systematic review, assessed methodological rigor, analyzed the results being reported in the selected studies. Condensed and organized the data before incorporating the findings into a comprehensive systematic review in narrative form. The distribution of J. altifrons in Indonesia is mainly in the Sumatra region, especially in the Northern and Central parts of the island. Taman Nasional Gunung Leuser (TNGL), Bukit Bungkuk Nature Reserve Forest and the surrounding lowland forests are good habitats. This species has habitat suitability at range elevations 20-500 meters (asl), very steep slopes (â‰¥ 45%). Optimal growth occurs under tree canopies, which provide the necessary shade for the plant to thrive. This suggests a specific habitat preference that influences its distribution